Implementasi Sistem Mulazamah dalam Pembelajaran Diniyyah di Madrasah Qur’aniyyah Al Husnayain Surakarta - Hanani, Hanif; Pamungkas, Maulana Al Bana; Azhari, Pebri (TSAQOFAH, 2024)
This article discusses the application of the mulazamah system in islamic learning to follow the previous scholars' learning system in order to improve the achievement of educational goals. The purpose of this study is to observe the learning process in its application. This investigation uses qualitative descriptive methods with data collection techniques through observations, interviews and documentation. It is also one of the programmes of support of the vision and mission of the Madrasah Qur’aniyyah Al Husanayain Surakarta that expects the emergence of a generation of Qur’anists who have the right to the Quran and Sunnah as well as the knowledge of religion and the establishment of hearts and akhlaq guided in the truth.